Active surveillance of Anaplasma marginale in populations of arthropod vectors (Acari: Ixodidae; Diptera: Tabanidae) during and after an outbreak of bovine anaplasmosis in southern Manitoba, Canada - Yunik, Matthew E.M. (Can J Vet Res, 2016)
Bovine anaplasmosis is the disease caused by the bacterium Anaplasma marginale. It can cause production loss and death in cattle and bison. This was a reportable disease in Canada until April 2014. Before then, infected herds were quarantined and culled, removing infected animals. In North America, A. marginale is biologically vectored by hard ticks (Acari: Ixodidae), Dermacentor variabilis and D. andersoni. Biting flies, particularly horse flies (Diptera: Tabanidae), can also act as mechanical vectors. An outbreak of bovine anaplasmosis, consisting of 14 herds, was detected in southern Manitoba in 2008. This outbreak lasted multiple rounds of testing and culling before eradication in 2011, suggesting local maintenance of the pathogen was occurring. We applied novel approaches to examine the vector ecology of this disease in this region. We did not detect A. marginale by screening of 2056 D. variabilis (2011 and 2012) and 520 horse flies (2011) using polymerase chain reaction (PCR).